Age‐specific differences in the magnitude of malaria‐related anemia during low and high malaria seasons in rural Zambian children. Issue 3 (4th June 2021) - Acheampong, Clement O.; Barffour, Maxwell A.; Schulze, Kerry J.; Chileshe, Justin; Kalungwana, Ng'andwe; Siamusantu, Ward; West, Keith P.; Palmer, Amanda C.
Abstract: Background: Malaria causes anemia by destruction of red blood cells and inhibition of erythropoiesis. Objective: We assessed whether the magnitude of the malaria‐specific effect on anemia differs by age, during low and high malaria seasons. Method: In rural Zambian children participating in a pro‐vitamin A efficacy trial, we estimated differences in the prevalence of anemia (defined as hemoglobin < 110 g/L for children < 60 months. and < 115 g/L in older children) by malaria status and assessed malaria‐age interactions. Regression models (with anemia as the outcome) were used to model malaria‐age interaction in both the low and high malaria seasons, controlling for potential confounders. Results: Average age was 68 months at baseline ( n  = 820 children). In the low malaria season, anemia prevalence was 29% in malaria‐negative children and 54% in malaria‐positive children ( p  < 0.001), with no malaria‐age interactions ( p  = 0.44). In the high malaria season, anemia prevalence was 41% in malaria‐negative children and 54% in malaria‐positive children ( p  < 0.001), with significant malaria‐age interactions ( p  = 0.02 for anemia). Age‐stratified prevalence of anemia in malaria positive versus negative children was 67.0% versus 37.1% (in children < 60 months); 57.0% versus 37.2% (in 60–69 months.); 46.8% versus 37.2% (in 70–79 months.); 37.0% versus 37.3% (in 80–89 months) and 28.0% versus 37.4% (in 90+ months). Conclusions: Malarial anemia is most severe in younger children, especially when transmission is intense. Anemia control programs must prioritize this vulnerable group.